Rozwiązane

pomocy
rozwiąż równanie kwadratowe
[tex](3x-2)^{2}-x^{2} -2x=1[/tex]



Odpowiedź :

Cześć ;-)

Rozwiązanie równania

[tex](3x-2)^2-x^2-2x=1\\\\9x^2-12x+4-x^2-2x-1=0\\\\8x^2-14x+3=0\\\\a=8, \ b=-14, \ c=3\\\\\Delta=(-14)^2-4\cdot8\cdot3=196-96=100\\\\\sqrt{\Delta}=\sqrt{100}=10\\\\x_1=\frac{-(-14)-10}{2\cdot8}=\frac{14-10}{16}=\frac{4}{16}=\frac{1}{4}\\\\x_2=\frac{-(-14)+10}{2\cdot8}=\frac{14+10}{16}=\frac{24}{16}=\frac{3}{2}=1\frac{1}{2}[/tex]

Użyte wzory

[tex](a-b)^2=a^2-2ab+b^2\\\\\Delta=b^2-4ac\\\\x_1=\frac{-b-\sqrt{\Delta}}{2a} \ \text{oraz} \ x_2=\frac{-b+\sqrt{\Delta}}{2a}[/tex]

Pozdrawiam!

Magda

Odpowiedź:

[tex](3x-2)^2-x^2-2x=1\\\\9x^2-12x+4-x^2-2x-1=0\\\\8x^2-14x+3=0\\\\\Delta=b^2-4ac=(-14)^2-4\cdot8\cdot3=196-96=100\\\\\sqrt{\Delta}=\sqrt{100}=10\\\\\\x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-14)-10}{2\cdot8}=\frac{14-10}{16}=\frac{4}{16}=\frac{1}{4}\\\\\\x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-14)+10}{2\cdot8}=\frac{14+10}{16}=\frac{24}{16}=\frac{3}{2}[/tex]